2008
DOI: 10.1039/b809721f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the potential of N-heterocyclic carbenes in molecular electronics: redox-active metal centers interlinked by a rigid ditopic carbene ligand

Abstract: Bimetallic homonuclear iron(II) and ruthenium(II) N-heterocyclic carbene complexes have been synthesized and crystallographically analyzed. As a spacer ligand for interconnecting the two redox-active metal centers, a ditopic carbene ligand has been used that comprises two carbene sites annelated to benzene. Detailed electrochemical and spectroelectrochemical analyses of the bimetallic systems revealed that despite the potentially p-delocalized nature of the ditopic ligand, the iron centers are only moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 43 publications
(28 reference statements)
6
60
0
Order By: Relevance
“…[14] Double metallation of the biscarbene precursor 9 with redox-active iron(II) centers has been accomplished via the freecarbene route to yield complex 10 (Scheme 2). [3] The analogous dinuclear ruthenium(II) complex 11 has been prepared by transmetallation from the corresponding silver(I) complex.…”
Section: Homobimetallic Benzobisimidazolylidene Complexesmentioning
confidence: 99%
“…[14] Double metallation of the biscarbene precursor 9 with redox-active iron(II) centers has been accomplished via the freecarbene route to yield complex 10 (Scheme 2). [3] The analogous dinuclear ruthenium(II) complex 11 has been prepared by transmetallation from the corresponding silver(I) complex.…”
Section: Homobimetallic Benzobisimidazolylidene Complexesmentioning
confidence: 99%
“…Spectroelectrochemical measurements further indicated that the mixed-valent Ru II /Ru III species and the fully oxidized Ru the apparently highly conjugated benzobis(imidazolylidene) bridging ligand C, the metal-metal interaction was mediocre at best. Different explanations for the weak coupling of the metal centers in this molecular configuration have been put forward, [16] including low d M -p L overlap due to a mismatch of the ligand 2p orbital and the metal 4d orbitals, [17] poor p electron delocalization between the arene and the NCN units in the bridging ligand, [18] and an unfavorable orientation of the relevant d M orbitals with respect to the p L system that mimizes overlap. [19] We have addressed this latter issue by incorporating rigid pyridyl donor groups into the NHC wingtips, which induce chelation and consequentially impart a coaxial arrangement of the metal and ligand orbitals, a concept that has been widely exploited in bipyridine chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This redox potential is about 0. [18] and thus demonstrates the lower electron density in the cationic chelates, which is also reflected in the NMR deshielding of the ligand protons (see above). No further oxidation occurred up to + 1.9 V. The cathodic current of the oxidation was considerably larger than the anodic current.…”
mentioning
confidence: 99%
“…The solid-state structures ( Figure 3) show piano stool geometry around the metal centres, with each metal bearing two chloride atoms, an NHC and either Cp* (2b) or p-cymene (6b). The M-Ccarbene bond lengths of 1.92(3) Å (2b) and 2.064(7) Å (6b) are relatively short when compared to other IrCp*(NHC)Cl2 and Ru(pcymene)(NHC)Cl2 complexes in the literature, 37,[41][42][43][44][45] which may be an effect of the carborane substituent causing the carbenic carbon to be more nucleophilic than other NHCs. Similarly to complex 3a, the Ir complex 2b underwent cyclometallation upon reaction with Ag2O in MeCN.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 97%